A bispecific antibody effectively neutralizes all four serotypes of dengue virus by simultaneous blocking virus attachment and fusion. Issue 3 (2nd April 2016) - Shi, Xin; Deng, Yongqiang; Wang, Huajing; Ji, Guanghui; Tan, Wenlong; Jiang, Tao; Li, Xiaofeng; Zhao, Hui; Xia, Tian; Meng, Yanchun; Wang, Chao; Yu, Xiaojie; et al.
ABSTRACT: Although dengue virus (DENV) infection severely threatens the health of humans, no specific antiviral drugs are currently approved for clinical use against DENV infection. Attachment and fusion are 2 critical steps for the flavivirus infection, and the corresponding functional epitopes are located at E protein domain III (E-DIII) and domain II (E-DII), respectively. Here, we constructed a bispecific antibody (DVD-1A1D-2A10) based on the 2 well-characterized anti-DENV monoclonal antibodies 1A1D-2 (1A1D) and 2A10G6 (2A10). The 1A1D antibody binds E-DIII and can block the virus attaching to the cell surface, while the 2A10 antibody binds E-DII and is able to prevent the virus from fusing with the endosomal membrane. Our data showed that DVD-1A1D-2A10 retained the antigen-binding activity of both parental antibodies. Importantly, it was demonstrated to be significantly more effective at neutralizing DENV than its parental antibodies both in vitro and in vivo, even better than the combination of them. To eliminate the potential antibody-dependent enhancement (ADE) effect, this bispecific antibody was successfully engineered to prevent Fc-γ-R interaction. Overall, we generated a bispecific anti-DENV antibody targeting both attachment and fusion stages, and this bispecific antibody broadly neutralized all 4 serotypes of DENV without risk of ADE, suggesting that it has great potential as a novel antiviral strategy against DENV.